PENGARUH KEPERCAYAAN DAN KOMITMEN TERHADAP LOYALITAS NASABAH PADA BANK PERKREDITAN RAKYAT TANAOBA LAIS MANEKAT KOTA KUPANG - Riven Agustien Tahun; Markus Bunga; Antonio E.L. Nyoko (Journal of Management Small and Medium Enterprises (SMEs), 2018)
This study aims to find empirical evidence on the influence of Trust and Commitment to CustomerLoyalty in Bank Perkreditan Rakyat Tanaoba Lais Manekat (BPR TLM) Kupang. Trust is measuredby reliability in achieving promise, trust for good service, trust for prompt service, trust to honesty ofpersonnel, trust of personnel in paying attention to customers. Commitment is measured by feelings ofemotional attachment, high sense of ownership, no influence on alternatives offered by other banks,feelings of pleasure to visit and employee friendliness. Loyalty is measured by Purchase Intention,Word-of-Mouth, Price Sensivity and Complaining Behavior. This research is a kind of causal researchto know the causal relationship. The sample in this research are 70 respondents. Sampling method inthis research is using Accidental Sampling. The analysis tools used are multiple regression analysis, Ftest and T test. The results showed that Trust and Commitment partially influence to the Loyalty ofBPR TLM’s Customer, as well as Trust and Commitment simultaneously affect the Loyalty of BPRTLM’s Customer.Keywords: Trust, Commitment, Loyalty